Perbedaan Intake Karbohidrat, Protein, Lemak, dan Kolesterol Antara Penderita Penyakit Jantung Koroner Dan Penyakit Jantung Non Koroner Pasien Rawat Jalan Di RSUD Dr Moewardi - Ekasari, Dyah Oktiva Furi; , Toto Suharto, SKM., M.Kes; , Endang Nur Widyaningsih, S.ST.,M.Si,Med (2013)
Background : Coronary heart disease is the primary cause of death in the world. The survey indicated that the heart disease and blood vessel show the highest cause of death are 26.3%. Objective : The purpose of the research was to determine the difference of carbohydrates, proteins, fats, and cholesterols intake between the patients of coronary and non-coronary heart diseases. Method : The design of the study was observational with cross sectional. The research was conducted for a month. The samples were evaluated in the study as much as 20 respondents of each kind of heart disease. The weight and height of samples have been assessed to find out their nutritional status. The carbohydrate, protein, fat, and cholesterol intake were determined using recall. Independent sample t-test was used in statistical analysis. Results : The result showed that most of respondents was more than 40 years (92.5%). Mostly education of respondents was high school (27.5%). The housewife was most of the respondent profession (25%). The HHD displayed the highest of coronary heart diseases, with precentage 27.5% of respondents. AP gave the same level with HHD, with precentage 27.5%. Based on stat analysis it was foud that there are no significant differences of carbohydrates, proteins, fat and cholesterols intake between the coronary and non-coronary heart diseases (p=0.101, p=0.070, p=0.670, p=0,460).